Community Socio-Cultural System in Bojonegoro District, East Java - Ramadhani, Alfafa Ramadhani; Faridatul Lailiyah; Rifai; Armawati Hidayati; Zahidah Mahroini; Insan Wastuwidya Mahardiani (International Journal of Geography, Social, and Multicultural Education, 2025)
Bojonegoro Regency, East Java, is an area with a rich culture that reflects a mix of ethnicities, traditions and local beliefs that have been passed down from generation to generation. This research aims to identify the socio-cultural elements of the Bojonegoro community as well as the impact of modernization on the local social structure and culture. The method used is a descriptive qualitative approach with data collection through literature study and participant observation. The research results show that the people of Bojonegoro still uphold the values ​​of mutual cooperation, traditional arts and traditional rituals which reflect a strong cultural identity. However, modernization through the oil and gas energy sector and information technology has triggered changes in consumption patterns, lifestyles and gender roles. Adaptation to these changes is seen through cultural innovation that remains rooted in traditional values. It is hoped that this study will become a reference in preserving local culture and formulating policies based on local wisdom.